Special Number or a Mere Numerical Array? Effect of Repdigits on Judgments and Choices - Honda, Hidehito; Matsunaga, Sota; Ueda, Kazuhiro (Frontiers in Psychology, 2020)
Previous studies have shown that people find special meaning in numerical arrays. In this article, we have focused on the features of numerical arrays, repdigits (e.g., “777”), and examined the effect of repdigits on judgments and choices. We formulated the following hypotheses: 1) when people want to assign special meanings to numbers (in the case of purchase or choice of alternatives that contain numbers [e.g., serial numbers]), repdigits will be chosen since people tend to prefer numbers that contain repdigits, and 2) when people think about probabilistic or statistical events involving numerical arrays, they will regard repdigits as a mere set of numerical arrays, and preference for them will disappear. Through five behavioral experiments, we examined these two hypotheses and the results generally supported them. We also discussed the features and psychological processes of repdigits in judgments and choices.